Monitoria: uma possibilidade de transformação no ensino-aprendizagem no ensino médio - Cunha Júnior, Fernando Rezende da (2009)
This work aims mainly at examining Monitory Activity as classroom organization in collaborative knowledge construction in six distinct subjects of the High School curriculum in a regular school in the South of Minas Gerais state. This work is based on Social-Historical-Cultural Activity Theory (Vygotsky, 2000; Leontiev, 1978; Engeström, 1999), which lead us to understand the organization and conception of Monitory Activity at school. It discusses some central concepts of Vygotsky s work, such as ZPD, Mediation, Meaning and Sense in order to understand the collaborative knowledge construction inside classroom, and questions concerning about Monitory (Faria, 2003; Cunha Jr., 2006b), which give us the possibility of understanding the functional part of Monitory Activity, as well as the Collaboration concept (Magalhães, 1998) applied to the Activity, and the language conception under Bakhtin s perspective (Bakhtin, 2000). This research is organized based on Critical Collaboration Research (Magalhães, 1998), being a process in which both researchers and subjects act effectively during the process of work realization. Data analyzed in this work were collected by audio-video recordings in meetings conducted with monitors and nonmonitors students, in distinct periods. There were also recorded classes with Monitory Activities, and the students also answered a questionnaire at the end of the first year of research. The results obtained show that Monitory Activity is an efficient way of classroom organization, as well as it gave a possibility of a new way to the students organization and engaging of teaching-learning process